Answer: -0.6 recurring
Step-by-step explanation:
-2/3 = -0.6 recurring
Hello there!
Yes, your solution is correct! A way to check it is replacing the value you found for x into x in the equation.
3(2-x) = 7 - 4x ⇒ 3(2-1) = 7 - 4(1)
And now solve 3(2-1) = 7 - 4(1).
3(1) = 7 - 4(1)
3 = 7 - 4
3 = 3
Since it is a true statement that 3 is equal to 3, it means your solution of x = 1 is correct. Good job! :)
Answer:
b 3x +7y =59
Step-by-step explanation:
x is water balloons at 3 each and y is t-shirts at 7$ each.
Charlie spent $89 more dollars on ice cream than on yogurt. He spent a total of $96 on ice cream and $7 on yogurt. If you subtract 7 from 96 you get 89.
$96- $7= $89
First month payment = $75
The amount to pay increases compound for the next 11 months
Number of months left on the instalment plan is 11 months
The increase is 6% = 0.06
Let F be final value and X be the value paid at the beginning of instalment, then
![F=X (1+0.06)^{n}](https://tex.z-dn.net/?f=F%3DX%20%281%2B0.06%29%5E%7Bn%7D%20)
, where 'n' is the number of months left to be paid